Number of teeth and chewing satisfaction related to cardiometabolic, vascular diseases and self-perception of health in older adults - Pedro, Rejane Eliete Luz; Jacondino, Camila Bittencourt; Rosemberg, Laura Schlatter; Schwanke, Carla Helena Augustin; Bós, Ângelo José Gonçalves; De Carli, Geralto Attilio; da Silva-Filho, Irenio Gomes (PAJAR - Pan-American Journal of Aging Research, 2014)
<span style="font-size: 12.0pt; line-height: 115%; font-family: 'Arial','sans-serif'; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Aims: To determine the association of chewing satisfaction and number of teeth with cardiometabolic and vascular diseases and self-perception of health (SPH) in the elderly. Methods: An observational and population-based cross-sectional study was conducted with the participating elderly of the Multidimensional Study of Elderly of Porto Alegre (EMIPOA) who responded to a questionnaire about their oral health, which was applied by telephone. The following variables were analyzed: sex, age, age range, chewing satisfaction, number of teeth, SPH, coronary artery disease (CAD), cerebrovascular accident (CVA), diabetes mellitus (DM), Hypertension (SAH) and obesity. Results: There were 251 elderly evaluated averaging on age 72.5±7.6 years. The mean number of teeth was 8.80±8.91 while chewing satisfaction was reported by 52.2%. A significant association (P<0.05) was observed between satisfaction with chewing ability and mean number of teeth, DM and SPH (dissatisfied elderly had a lower mean number of teeth, poor/awful SPH and greater prevalence of DM). A significant association was also observed between mean number of teeth and age range, SPH, CVA, CAD, SAH (lower mean number of teeth in elderly ≥80 years and with fair/poor perception of health and the morbidities described). Conclusions: In the elderly of EMIPOA, oral health was found to be associated with age range, cardiometabolic and vascular diseases and self-perception of health.